Community Life and International Multiculturalism in The Development of Sangha Education at The Mahavihara Buddha Plum Village Thailand - Bawana Putra; Burmansah Burmansah; Wistina Seneru (Universitas Sebelas Maret, 2025)
The development of Sangha education in the modern era is strongly influenced by two main factors, namely community life and international multiculturalism. Community life has an important role in helping individuals, especially Sangha members, in the process of self-development and continuous inner transformation. Meanwhile, international multiculturalism encourages openness and acceptance of the diversity of different cultural backgrounds, languages, and customs, which ultimately enriches spiritual experiences and broadens the horizons of Sangha members in undergoing religious practices. This research aims to explore the influence of community life and international multiculturalism on the development of Sangha education, by taking acase study at Mahavihara Plum Village Thailand. The method used is descriptive quantitative, involving 100 respondents from among the monastic Sangha, who were selected using proportional random sampling technique. The research instrument was a questionnaire. Data were analysed using various statistical techniques, including validity, reliability, classical assumptions, multiple linear regression F test, and t test. The results show that community life has a significant effect on the development of Sangha education (tcount = 8.402, significance = 0.000), while international multiculturalism provides a lower effect (tcount = 1.811, significance = 0.007). The R Square value of 0.889 indicates that the combined contribution of community life variables and international multiculturalism to the development of Sangha education reaches 88.9%. In other words, understanding and application of community life values and openness to international multiculturalism play a very dominant role in shaping and directing the direction of the development of Sangha education, especially in the context of Mahavihara Plum Village Thailand. Meanwhile, the remaining 11.1% is influenced by other factors that are beyond the scope of this study.